Espectroscopia por ressonância magnética de prótons em epilepsia mioclônica juvenil sugere o comprometimento de uma rede neuronal específica - Lin,K. (2008)
OBJECTIVES: The neuroanatomical basis and the neurochemical abnormalities that underlay juvenile myoclonic epilepsy (JME) are not fully defined. While the thalamus plays a central role in synchronization of widespread regions of the cerebral cortex during a seizure, emerging evidence suggests that all cortical neurons may not be homogeneously involved. The purpose of this study was to investigate the cerebral metabolic differences between patients with JME and normal controls. METHODS: All patients had a JME diagnosis based on seizure history and semiology, EEG recording, normal magnetic resonance neuroimaging (MRI) and video-EEG. Forty JME patients (JME-P) were submitted to 1.5 T MRI proton spectroscopy (1H-MRS), multi-voxel with PRESS sequence (TR/TE = 1500/30 ms) over the following locations: prefrontal cortex (PC), frontal cortex (FC), thalamus, basal nuclei, posterior cingulate gyrus (PCG), insular, parietal and occipital cortices. We determined ratios for integral values of N-acetyl aspartate (NAA) and glutamine-glutamate (GLX) over creatine-phosphocreatine (Cr). The control group (CTL) consisted of 20 age and sex-matched healthy volunteers. RESULTS: Group analysis demonstrated a tendency for lower NAA/Cr ratio of JME-P compared to CTL predominantly on FC, PC, thalamus and occipital cortex. When compared to CTL, JME-P had a statistically significant difference in GLX/Cr on FC, PC, insula, basal nuclei, PCG and on thalamus. When evaluating the relationship among the various components of this epileptic network among JME-P, the strongest correlation occurred between thalamus and PC. Also, we found a significant negative correlation between NAA/Cr and duration of epilepsy. CONCLUSION: Reductions in NAA may represent loss or injury of neurons and/or axons, as well as metabolic dysfunction while glutamate is considered to be an excitatory neurotransmitter in the brain which is involved in the pathogenesis of epileptogenic seizures.